2009
DOI: 10.1371/journal.pone.0004164
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Electrostatic Landscape of Class II Human Leukocyte Antigen Molecule Induced by Modifications in the Myelin Basic Protein Peptide: A Theoretical Approach

Abstract: The receptor-ligand interactions involved in the formation of the complex between Class II Major Histocompatibility Complex molecules and antigenic peptides, which are essential for establishing an adaptive immunological response, were analyzed in the Class II Human Leukocyte Antigen (HLA) - Myelin Basic Protein (MBP) peptide complex (HLA-DRβ1*1501-MBP) using a multipolar molecular electrostatic potential approach. The Human Leukocyte Antigen - peptide complex system was divided into four pockets together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To further investigate the flexibility origin with respect to the five binding pockets (Fig. 3A) traditionally defined in the binding site [45], we divided the binding groove into four compartments (Fig. 3B), covering most of the peptide-binding pockets and analyzed the structural changes in each one, for the free and bound alleles (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the flexibility origin with respect to the five binding pockets (Fig. 3A) traditionally defined in the binding site [45], we divided the binding groove into four compartments (Fig. 3B), covering most of the peptide-binding pockets and analyzed the structural changes in each one, for the free and bound alleles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical studies have used variations in the electrostatic landscapes of MHC class II binding groove to distinguish the pockets' amino acids with a specific anchoring (Pocket 1 and 4) or recognition (Pockets 4 and 7) property (Fig. 3A) [45]. Moreover, preferences in peptide-binding shown by different HLA-DRB1 allele variants, suggest also a relevant role of the residues surrounding the pockets in disease susceptibility [36].…”
Section: Introductionmentioning
confidence: 99%
“…A multipolar molecular electrostatic potential analysis of the receptor-ligand interactions involved in the formation of the complex between HLA class II molecules and antigenic peptides (HLA-DRB1⁎ 1501-MBP) disclosed that amino acids occupying the polymorphic positions beta13R, beta26F, beta28D, beta9W, beta74A, beta47F and beta57D are relevant for this receptor-ligand interaction [35], which could have potential predictive and therapeutical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wucherpfennig and Strominger [24] suggested that MBP residues K93, F91, and H90 are primary TCR contact points. Therefore, we confirm that *14∶01 allele is showing a quite distinct capability to anchor the MBP peptide in pocket 4, with respect to *03∶01, particularly for residue K93, likely impacting on TCR recognition and ultimately in T cell triggering and activation.…”
Section: Discussionmentioning
confidence: 99%